Pemahaman Siswa Terhadap Penyimpangan Perilaku Seksual Dikalangan Remaja SMK - Yora Chantika; Linda Fitria; Rini Sefriani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In problematic adolescents who are controlled by aggressive and antagonistic urges, the sensitivity to the effects of deviant sexual behavior will generally be higher. Adolescents of this type will channel their curiosity about sex through reading